Playful Communication and Care: Exploring Child-Centred Care of Young Children With Type 1 Diabetes Through the Framework of Zone of Proximal Development - DeCosta, Patricia; Grabowski, Dan; Jespersen, Louise Norman; Skinner, Timothy C. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Introduction: Little is known about the psychosocial experiences and care needs of young children under the age of 7 years who have been diagnosed with type 1 diabetes. To address this knowledge gap, we examine children’s psychosocial care needs through the lens of child-centred care and the framework of Zone of Proximal Development. Objectives: To explore current care practices for young children with diabetes and identify aspects of child-centred care already successfully integrated into current practice. Method: Individual face-to-face, semi-structured interviews were conducted with 20 Healthcare Professionals, representing 11 of 17 paediatric diabetes clinics in Denmark. Results: Our data provided valuable insights into existing child-centred practices. Our analysis identified practices covering four main themes: 1. Accommodating immediate emotional needs, 2. Putting children before diabetes, 3. Encouraging meaningful participation, 4. Playful communication. Discussion: Healthcare Professionals provided child-centred care, largely through play-based approaches that make diabetes care meaningful and relevant. Such practices provide the scaffolding necessary to enable young children to gradually engage, comprehend and participate in their own care.